Factors Affecting Entrepreneurial Intention of Business Students: Case Study of VNU University of Economics and Business - Mai, Nguyen Phuong; Ngoc, Luu Thi Minh; Linh, Dao Thi Phuong; Lan, Nguyen Thi; Quynh, Tran Thi Ngoc (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2018)
This paper presents results of a research on determinants of entrepreneurial intention among business students. VNU – University of Economics and Business is chosen for survey location. 250 questionnaires were emailed to business students at VNU – UEB, and then 226 responses were valid for further analysis. Findings from this research show that knowledge and experience, attitude toward entrepreneurship and perceived behavior control are three most important factors that influence the entrepreneurial intention.